Effect of Tannic Acid and Metal Salts on Dyeing of Woolen Fabrics with Red Onion (Alliumcepa L.) - Gümrükçü, Gülsah; Üstün Özgür, Mahmure (Asian Journal of Chemistry, 2010)
A natural dye (anthocyanins) was extracted from red onion (Alliumcepa L.) using different buffers as extractant at 25 ºC for 20 min. The amount of total anthocyanins was determined by using the derivative spectrophotometric method. The dyeing behavior of these colour components on wool has also been evaluated. Dyeing processes were carried out using the mordant mixtures (tannic acid + metal salts) according to pre- and post-mordanting methods by using buffer solutions at pH 2-8 for 1 h at 98-100 ºC with open bath dyeing technique. Colour differences in CIE L*a*b* unit and gray scale classifications are reported. Dyeing conditions and other characteristics show that the mordant mixture is more beneficial than dye as it shows good light fastness and antibacterial property. The dye obtained from the red onion may be alternative source to synthetic dyes for the dyeing of wool.